ASSOCIATION BETWEEN BLOOD PRESSURE VARIABILITY AND EARLY NEUROLOGICAL DETERIORATION IN ACUTE ISCHEMIC STROKE PATIENTS - Ike Retno Yolanda, Khairul Putra Surbakti, Alfansuri Kadri (International Journal of Research Science and Management, 2020)
Background: Variability in blood pressure is a predictor of stroke severity and causes of poor functional outcome. Blood pressure variability is one of the main predictor of the prognosis acute ischemic stroke. Blood pressure variability were independently and linearly associated with the development of early neurologic deterioration (END) in acute ischemic stroke Objective: To determine the association between blood pressure variability and END in acute ischemic stroke patients. Method: This study uses a cross sectional design. Sampling was conducted at H. Adam Malik General Hospital Medan. Samples were taken as many as 40 subjects consecutively. Blood pressure checks were perform every hour for 72 hours then an assessment of the National Institute of Health Stroke Scale (NIHSS) score at admission and the third day of treatment. Data analysis used fisher’s exact test. Results: The demographic characteristics of the study subjects were an average age of 56-<71 years, high school education level, housewife occupation and Batak ethnicity. The mean of maximum systolic blood pressure (SBP) was 151±12.16 mmHg, minimum SBP 123.15±18 mmHg, delta SBP 25.35±10.66 mmHg, maximum diastolic blood pressure (DBP) 79.7±6.01 mmHg, minimum DBP 61.77±7.32 mmHg and delta DBP 17.97±8.48 mmHg. The NIHSS day 1 score had an average of 9.55±6.73, the NIHSS day 3 score was 11.25±7.93. Most subjects experienced END. There is a significant relationship between blood pressure variability and END with a p of 0.03 (p<0.05). Conclusion: There is a significant relationship between blood pressure variability and END in patients with acute ischemic stroke.